Synthesis and Characterization of New Aromatic Polyesters Derived from New Aromatic Di- and Tri Hydroxyl Monomers with 4-Phenylenediacrylic Acid and Malonic Acid - A. Mutar, Mohammed (Asian Journal of Chemistry, 2014)
In the present work, six new aromatic polyesters (PE1-PE6) have been synthesized in high yields from the polycondensation between di- and tri hydroxyl monomers containing methylene unit, Schiff-base linkages and pyridine heterocyclic ring with 4-phenylenediacrylic acid and malonic acid using dibutyltin dilaurate as catalyst. The structure analysis of the polymers has been carried out by using FT-IR and 1H NMR spectroscopy. The monomers were characterized by FTIR and 1H NMR. FT-IR technique confirmed the esterification of di and tri hydroxyl monomers by the acid in all the polymers.